2003
DOI: 10.1051/0004-6361:20030441
|View full text |Cite
|
Sign up to set email alerts
|

Substructures and galaxy orientations in clusters II. Cluster Abell 14

Abstract: Abstract. We present an investigation of the Abell 14 galaxy cluster, including a discussion of subclustering, some aspects concerning its evolution, as well as an analysis of galaxy orientations in the cluster region. We confirm the previous results showing evidence for subclustering in this cluster obtained from studies of galaxy distributions. In this light, our aim has been to examine non-random effects in the galaxy orientations in rich clusters, with particular regard to the presence of subclustering. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…In the appendix of FG they describe how to derive the SV orientation of a galaxy and we followed their method. FG's method has been applied by several authors in galaxy orientation studies (KO; Go93; Go94; Hu et al 1995;Wu et al 1997;Yuan et al 1997;Hu et al 1998;Godlowski & Ostrowski 1999;Aryal & Saurer 2000 (AS); Aryal & Saurer 2001;Flin 2001;Baier et al 2003;Aryal & Saurer 2004). In their method, the three dimensional orientation of the SV of a galaxy is characterized by two angles: the polar angle (θ) between the galactic SV and a reference plane, and the azimuthal angle (φ) between the projection of a galactic SV on to this reference plane and the X-axis within this plane.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In the appendix of FG they describe how to derive the SV orientation of a galaxy and we followed their method. FG's method has been applied by several authors in galaxy orientation studies (KO; Go93; Go94; Hu et al 1995;Wu et al 1997;Yuan et al 1997;Hu et al 1998;Godlowski & Ostrowski 1999;Aryal & Saurer 2000 (AS); Aryal & Saurer 2001;Flin 2001;Baier et al 2003;Aryal & Saurer 2004). In their method, the three dimensional orientation of the SV of a galaxy is characterized by two angles: the polar angle (θ) between the galactic SV and a reference plane, and the azimuthal angle (φ) between the projection of a galactic SV on to this reference plane and the X-axis within this plane.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The lack of knowledge of PAs of nearly face-on galaxies and an inhomogenous distribution of positions of galaxies are the main selection effects (Baier et al 2003;Aryal & Saurer 2005). It is essential to remove both the positional and inclination effect from the database.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Baier et al (2003) published their study of galaxy orientations in Abell 14. They found strong evidence for the alignment of galaxy position angles (PAs) in the clusters in the sense that the major planes of galaxies tend to be parallel to the direction of the PA of the major axis of the cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Godlowski et al (1998) and Baier et al (2003) used similar selection criteria and methods but found an opposite result for the clusters Abell 754 and Abell 14. Godlowski et al (1998) found that the angular momenta of the galaxies in the cluster Abell 754 are preferentially aligned parallel with the cluster plane.…”
Section: Introductionmentioning
confidence: 97%
“…There are two camps in the field of galaxy orientation studies: one of these is searching for nonrandomness of the orientations of galaxies in the Local Supercluster (hereafter LSC) plane (e.g., Reinhardt & Roberts 1972;Jaaniste & Saar 1978, hereafter JS;MacGillivray et al 1982;Kapranidis & Sullivan 1983;MacGillivray & Dodd 1985a,b;Flin & Godlowski 1986, hereafter FG;Kashikawa & Okamura 1992, hereafter KO;Godlowski 1993, hereafter Go93;Godlowski 1994;Yuan et al 1997;Hu et al 1998). The other research direction is the investigation of the orientations of galaxies in other clusters (e.g., Hawley & Peebles 1975;Thompson 1976;MacGillivray et al 1982;Helou & Salpeter 1982;Djorgovski 1983Djorgovski , 1987Hoffman et al 1989;Trevese et al 1992;Hu et al 1995;Wu et al 1997;Godlowski et al 1998Godlowski et al , 1999Baier et al 2003), particularly in the well studied Virgo cluster (e.g., Hawley & Peebles 1975;Thompson 1976;MacGillivray et al 1982;Helou & Salpeter 1982;Djorgovski 1987;Hoffman et al 1989;Hu et al 1995) and Coma cluster (e.g., Hawley & Peebles 1975;Thompson 1976;Djorgovski 1987;Wu et al 1997;Flin 2001).…”
Section: Introductionmentioning
confidence: 99%